PEMBENTUKAN PERATURAN DAERAH PERSPEKTIF GENDER (ANALISIS TERHADAP PEMBENTUKAN PERATURAN DAERAH PERSPEKTIF GENDER DI PROVINSI NUSA TENGGARA BARAT KURUN WAKTU 2013-2016): Analisis Terhadap Pembentukan Peraturan Daerah Perspektif Gender di Provinsi Nusa Tenggara Barat Kurun waktu 2013-2016 - Sidiq, Gazali (Universitas Islam Negeri Raden Fatah Palembang, 2019)
The main problem for seeking the substance of legislation includes technical operational policies that are sensitive and responsive to various problems in society, including the issue of gender inequality practical and strategic steps to create and realize legislation whose content is sensitive and responsive to gender so that everything the problems and aspirations of the community can be accommodated in a form of regulation that is also gender responsive. Integrating gender perspective into legislation to realize prosperity. The aim is envisioned by the wider community. The legislation can be in the form of a law along with its implementing regulations and regional regulations along with the implementing regulations. Keywords : Hakam, Pengadilan Agama, Mahkamah Syar’iyyah.